Induction of polycystic ovary model through one-time injection of estradiol valerate in female adult rats in animal laboratory of Aja University of Medical Sciences - Beheshteh Abouhamzeh; Mohammad Farhadi; Maasoume Abdollahi (فصلنامه ابن سینا)
Background and aims: One of the most common endocrine disorders affecting females during their reproductive years is polycystic ovary syndrome (PCOS), which is associated with symptoms such as dysmenorrhea, infertility, hirsutism, acne, and obesity. This study aimed to induce a polycystic ovary model in female adult rats through a single injection of estradiol valerate. Methods: In this experimental study, 50 adult female rats were divided into four groups: PCO+1 (N=15), PCO+2 (N=15), control (N=10), and sham (N=10). The PCO+1 and PCO+2 groups received subcutaneous injections of estradiol valerate at doses of 1 mg and 2 mg, respectively, combined with 0.2 ml of olive oil. The sham group received a subcutaneous injection of 0.2 ml of olive oil, while the control group underwent no intervention. Body and ovarian weights were measured, and histological analyses were performed to count ovary follicles. Results: A significant increase in weight was observed in the PCO+2 group compared to the other groups. The numbers of primary, secondary, and mature follicles, as well as corpora lutea, were lower in the PCO+2 group compared to the others. However, there was no significant difference in the number of atretic follicles. Notably, the PCO+2 group showed a significant increase in the number of cystic follicles compared to the other groups. Conclusion: The results of this study indicate that a single injection of 2 mg of estradiol valerate effectively induces a polycystic ovary model, characterized by the presence of cystic follicles and a reduction in mature follicles.